Historical sociology: limitations and perspectives - Koenig, Matthias (European journal of sociology, 2006)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0003975606000130/resource/name/firstPage-S0003975606000130a.jpg